Examining the Anatomy of a Screencast: Uncovering Common Elements and Instructional Strategies - Sugar, William; Brown, Abbie; Luterbach, Kenneth (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
The researchers engaged in cooperative inquiry in order to explore screencasts as online instructional tools. In total, each researcher analyzed 37 screencasts, which provided over two hours of instruction. The content area of these screencasts concentrated on teaching specific computing procedures (e.g., how to install web server software or how to add a table in a word processor). The researchers analyzed their own self-produced screencasts as well as those that were professionally produced. Analyses of the screencasts led the researchers to discover common structural components (i.e., bumpers, screen movement, and narration) and common instructional strategies (i.e., provide overview, describe procedure, present concept, focus attention, and elaborate content). By synthesizing the common structure and common instructional strategies, the researchers offer a framework for considering the role of screencasts as online instructional tools. To introduce a practical application of the framework, the researchers created a screencasting checklist, which may be used by online instructors and instructional designers to develop and assess their own screencasts. This initial work invites additional research and development in order to refine the screencasting framework and checklist.